1995
DOI: 10.1007/bf00355644
|View full text |Cite
|
Sign up to set email alerts
|

CpG island clones for Chromosome 11p?a resource for mapping and gene identification

Abstract: A NotI end fragment library has been constructed for human Chromosome (Chr) 11p. Seventy-two clones were mapped to chromosomal subregions by use of somatic cell hybrids. The clones detect 44 different CpG islands, and we have isolated cosmid contigs for 36 of them. Extrapolation from the known 11p13 NotI restriction map suggests that every second CpG island from 11p containing a Not site is already represented in the clone collection. By sequence analysis all of the 11p13 clones exhibit typical features of CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Until the complete sequence of human 11p13 becomes available, the presence of other genes between WT1 and PAX6 remains a possibility. To date, however, despite intense study (15,(19)(20)(21), no other genes have been found in this region in man. It is interesting that the Fugu homolog of this human region, which exhibits a low density of CpG islands, shows greater than average size reduction, consistent with Fugu counterparts of gene-poor regions exhibiting the greatest compaction (2).…”
Section: Resultsmentioning
confidence: 99%
“…Until the complete sequence of human 11p13 becomes available, the presence of other genes between WT1 and PAX6 remains a possibility. To date, however, despite intense study (15,(19)(20)(21), no other genes have been found in this region in man. It is interesting that the Fugu homolog of this human region, which exhibits a low density of CpG islands, shows greater than average size reduction, consistent with Fugu counterparts of gene-poor regions exhibiting the greatest compaction (2).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore, termed this new murine gene four-jointed x1 (fjx1). Partial fjx1 cDNA clones were isolated from an embryonic day (E) 8.5 mouse embryo cDNA library using a human genomic probe from chromosome 11p13 (Thate et al, 1995). Since the human gene does not contain an intron Mechanisms of Development 80 (1999) 213-217 0925-4773/99/$ -see front matter © 1999 Elsevier Science Ireland Ltd. All rights reserved.…”
Section: Resultsmentioning
confidence: 99%
“…An E8.5 day mouse embryo cDNA library (a gift of B. Hogan) and a mouse genomic library (strain 129SVJ) were screened with a 1.7 kb NotI-BamHI fragment from the human NE3 locus (D11S3892) using standard conditions except for a reduced hybridization and washing temperature of 55°C (Sambrook et al, 1989). The isolation of the human genomic probe was described in Thate et al, 1995. The region homologous to fjx1 was sequenced and a 2088 bp Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Of interest, both WT1 28 and myoD 29 genes are found in chromosome 11p, a region noted for the presence of CpG islands. 30 CpG islands may contain methylated cytosine, a molecule responsible for parental imprinting by which maternally or paternally derived genes switch off expression of derivative RNA. 31 Abnormalities in imprinting were found to be common in embryonal neoplasms, tumors that look similar to embryonal tissues.…”
Section: Historical Use Of Ancillary Testingmentioning
confidence: 99%